Using Community Conversations to explore animal welfare perceptions and practices of rural households in Ethiopia - Lemma, Mamusha; Doyle, Rebecca; Alemayehu, Gezahegn; Mekonnen, Mesfin; Kumbe, Adem; Wieland, Barbara (Frontiers in Veterinary Science, 2022)
There is a scarcity of data on animal welfare and its impact on livelihoods to inform animal welfare initiatives in Ethiopia. Perceptions and practices of rural households toward animal welfare are influenced by socio-cultural, demographic, and agroecological factors. We conducted Community Conversations in two geographically and culturally diverse regions of Ethiopia to explore the attitudes and practices of rural households regarding animal welfare and its impact on livelihoods. Community Conversations are facilitated dialogues among rural households to explore their perceptions, practices, constraints, and needs and identify and co-create solutions to improve the welfare of their animals. We used single- and mixed-sex discussion groups to understand community members’ gendered perceptions of animal welfare and influence their attitudes and practices toward gender-equitable roles in animal welfare management. In the Community Conversations, community members readily described the biological needs of their animals but there was also a good acknowledgment of the behavioral and affective state needs of animals. Identified constraints for animal welfare included feed and water shortage, limited veterinary support, and poor animal handling practices. Community members described the welfare of their animals as being intertwined with their own livelihoods and identified productive, public health, and non-economic benefits of good animal welfare. Raising awareness of animal welfare within rural communities through Community Conversations is a useful way to both identify livestock production needs as well as engage community members in making practical improvements in animal welfare. The understanding of perceptions, practices, and needs of rural households in animal welfare helps engage communities in starting behavioral change and provides insights into developing context-specific welfare improvement interventions. Community Conversations are also an effective way to feedback community voices into planning to build a bottom-up implementation of animal welfare programs.